FUNDAMENTALS FOR SELF-TAUGHT PROGRAMMERS embark on your software engineering journey without exhaustive courses and bulky tutorials - Greenaway, Jasmine (PACKT PUBLISHING LIMITED, 2023)
An absolute beginner's guide to strengthening the fundamentals before learning your first programming language Purchase of the print or Kindle book includes a free PDF eBook Key Features Explore fundamental computer science concepts from data structures through to object-oriented programming Progress from understanding the software engineering landscape to writing your first program Authored by a Microsoft community insider and filled with case studies from software engineering roles Book Description Software engineering is a set of techniques, including programming, within the computer science discipline associated with the development of software products. This practical guide to software engineering will enable aspiring and new developers to satisfy their curiosity about the industry and become ready to learn more about the basics before beginning to explore programming languages, along with helping junior and upcoming developers to effectively apply their knowledge in the field. The book begins by providing you with a comprehensive introduction to software engineering, helping you gain a clear, holistic understanding of its various sub-fields. As you advance, you'll get to grips with the fundamentals of software engineering, such as flow control, data structures and algorithms. The book also introduces you to C# and guides you in writing your first program. The concluding chapters will cover case studies, including people working in the industry in different engineering roles, as well as interview tips and tricks and coding best practices. By the end of this programming book, you'll have gained practical knowledge of the implementation and associated methodologies in programming that will have you up and running and productive in no time. What you will learn Gain an understanding of the software engineering landscape Get up and running with fundamental programming concepts in C# Implement object-oriented programming (OOP) in C# Gain insights on how to keep the code readable and reusable Discover various tips and tricks to efficiently prepare for a software engineering interview Implement various popular algorithms using C# Who this book is for This book is for anyone who is curious about programming and interested in entering the field of software engineering by beginning at the fundamentals. No prior knowledge of computer science or software engineering is necessary.